2019
DOI: 10.1007/s40520-019-01190-x
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring physical performance in highly active older adults: associations with age and gender?

Abstract: Background: Higher age is associated with reduced physical capability in the general population. The role of age and gender for physical performance in older adults who exercises regularly is however not clear, and there is also a lack of recommendations for outcomes to address physical performance for this population. Aims: To explore the associations between physical performance, age and gender, and to examine the suitability and feasibility of clinical field tests for physical performance in active older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
3
29
0
3
Order By: Relevance
“…There is strong evidence that physical activity reduces the risk of falling [ 27 , 28 ]. Some papers have also pointed out that physical activity is more intense and frequent in elderly men, while activities of daily living are usually more demanding for women [ 29 ]. Unfortunately, in our study we have not recorded a validated score for physical activity, but the participants who were men reported practicing more physical activity than women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is strong evidence that physical activity reduces the risk of falling [ 27 , 28 ]. Some papers have also pointed out that physical activity is more intense and frequent in elderly men, while activities of daily living are usually more demanding for women [ 29 ]. Unfortunately, in our study we have not recorded a validated score for physical activity, but the participants who were men reported practicing more physical activity than women.…”
Section: Discussionmentioning
confidence: 99%
“…This is the only factor that could explain our results. Comorbidity, medication or socioeconomic differences, other important-factors mentioned in the literature as responsible for poor balance [ 29 31 ] should not be taken into account in our present work because we selected for healthy subjects, unhealthy were excluded, and they were mostly couples with a similar socioeconomic status. Nevertheless, despite the oral report of physical activity, due to the absence of a systematic collection of this information through self-reports or administered scales, we consider that one should take with caution the interpretation that the differences in balance score between genders is due to differences in levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following variables that could potentially impact muscle health and nutritional status according to the literature [19,[31][32][33][34][35][36][37] were considered covariates: age, sex, smoking status (yes/no), alcohol consumption (yes/no), number of comorbidities per individual, number of drugs consumed per individual, cognitive status assessed by the Mini-Mental State Examination (MMSE) [38], self-reported physical activity level with the Minnesota Leisure Time Activity Questionnaire [39], and the baseline value of the muscle component.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Additionally, some risk factors of falls have gender differences, which might contribute differently to falls. For example, studies have found that females experience higher fear of falling than males (Hewston & Deshpande, 2018), while men possess better muscle strength and balance than females (Tangen & Robinson, 2020). Understanding the risk factors of falls and the gender differences in Asian OWD deserve special attention.…”
Section: Introductionmentioning
confidence: 99%